Learning styles of the Armed Forces of Ukraine personnel undergoing English language courses - Roman V. Duzhyi; Tetiana M. Derkach (Academy of Cognitive and Natural Sciences, 2024)
The preferred learning styles according to the Felder-Soloman method of military personnel of the Armed Forces of Ukraine with various military ranks studying English on four-month face-to-face foreign language courses based on the Foreign Languages Education and Research Center of the National Defense University of Ukraine were studied. Active, sensing and visual styles account for approximately 85% of students, while the remaining 15% have reflective, intuitive and verbal styles. The advantage of the sequential over global style is about 75%. No correlation was found between individual learning preferences, the results of the English language entrance test (four tests - listening, writing, reading and speaking), and officer ranks. The method of two-stage cluster analysis shows that respondents form two clusters (Silhouette cluster quality - 0.5-0.6) of approximately the same size according to the level of language proficiency. The most influential factor for cluster formation is the results of listening. Military personnel learning styles were compared with literature data on students' learning styles from 12 fields of study. Two fields (military and natural sciences) demonstrate the preferences toward four styles in all four dimensions; preferences in 2 directions (sensing and visual) and balance in the other two are characteristic of six fields of study. Four other studied fields have a propensity in only one dimension (visual perception of information).